General banking activities and advance section of banking operation- observation of Laboratory Road Branch, Dhaka - Wahid, Labib Saad (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.